2018
DOI: 10.1177/1060028018815064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Targeted Pharmacist Interventions to Reduce Length of Stay in an Acute Care Practice Model

Abstract: Background: Despite widespread recognition of the need for innovative pharmacy practice approaches, the development and implementation of value-based outcomes remains difficult to achieve. Furthermore, gaps in the literature persist because the majority of available literature is retrospective in nature and describes only the clinical impact of pharmacists’ interventions. Objective: Length of stay (LOS) is a clinical outcome metric used to represent efficiency in health care. The objective of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…DG8 was also identified as a practice priority in Egypt ( International Pharmaceutical Federation, 2022 ). The added value of a pharmacist in multidisciplinary intra- and inter-professional healthcare teams was highlighted in several studies ( Bond and Raehl, 2007 , Leary et al, 2019 , Zhai et al, 2016 ). However, findings from the present study were similar to other studies in the region that showed the limited participation of pharmacists in multidisciplinary healthcare services ( Chamoun et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…DG8 was also identified as a practice priority in Egypt ( International Pharmaceutical Federation, 2022 ). The added value of a pharmacist in multidisciplinary intra- and inter-professional healthcare teams was highlighted in several studies ( Bond and Raehl, 2007 , Leary et al, 2019 , Zhai et al, 2016 ). However, findings from the present study were similar to other studies in the region that showed the limited participation of pharmacists in multidisciplinary healthcare services ( Chamoun et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, psychological interventions effectively alleviate the pressure on patients and enhance their confidence in overcoming the disease. Results of LEARY demonstrated that targeted intervention plus comprehensive nursing enhances patients' treatment compliance, establishes a good nurse-patient relationship, and helps the patients cultivate a healthy lifestyle, which shows great prognosis benefits [ 19 ]. Clinical research has found a strong association between nursing satisfaction and the allocation of medical staff, which highlights the rational use of human resources to ensure the quality of care and improve nursing satisfaction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a broad range of hospital pharmaceutical services, clinical pharmaceutical service systems established by various countries, as exemplified by the systems established in developed countries such as the United States and Japan ( Pharmacy ACOC, 2008 , American College of Clinical P, 2014 , Zhu and Shang, 2015 , Shen, 2017 ), also administer community pharmacy services and derivative household pharmaceutical services ( Evans et al, 2017 ). Furthermore, by promoting rational drug use, pharmacists can reduce patients' risk of hospitalization and re-hospitalization, lessen risks of infection, and play an active role in diagnosis and treatment ( Leary et al, 2019 , Readdean et al, 2018 , Shao, 2008 ).…”
Section: Introductionmentioning
confidence: 99%